Palm olein-in-water cream containing extracts from Hirudinaria manillensis for improving blood flow - Abdul Talib, Mat Sharil; ., Maryanto; Taher, Muhammad; Md. Jaffri, Juliana; Ahmad, Kausar (2011)
The Malaysian leech variety, Hirudinaria manillensis, has an anticoagulant known as hirudin. Due to this, products containing extract from leech can be obtained in the market mainly in the form of oil or ointment to treat ailments associated with poor blood flow. A cream product using refined, bleached and deodorized palm olein containing the extract of H. manillensis was prepared for improving the blood circulatory system using a suitable combination of surfactants. Cream is suggested because of its convenient application and fewer side effects compared to injection and oral dosage forms. Topical cream preparation may be an alternative to the commercially-available anticoagulant in terms of a more convenient application and with reduced side effects or complications. There is also a possibility that the formulation may become an over-the-counter drug (OTC)' Extraction of H. mannilensis was done using acetone/ acid and was purified by 5o% ammonium sulfate.